Prevalence and factors associated with alcohol consumption among persons with diabetes in Kampala, Uganda: a cross sectional study - Maki Sifa Salama; Jonh Bosco Isunju; Salama Kaishusha David; Fiston Muneza; Sylvester Ssemanda; Nazarius Mbona Tumwesigye (BMC, 2021)
Abstract Background The prevalence of diabetes has been rising increasing rapidly in middle- and low-income countries. In Africa, the World Health Organization projections anticipate diabetes mellitus to be the seventh leading cause of death in by 2030. Alcohol consumption influences diabetes evolution, in such a way that it can interfere with self-care behaviours which are important determinants of diabetes prognosis. In this study, we evaluated factors associated with alcohol consumption among persons with diabetes in Kampala to inform management policies and improve comprehensive diabetes care. Methodology A cross-sectional study was conducted systematically among 290 adults with diabetes, attending diabetic clinics at Mulago National Referral Hospital and St Francis Hospital Nsambya. Data were entered and analysed in Epi-Info version 7 and STATA 13 software. Modified Poisson regression was used to identify factors associated with alcohol consumption among persons with diabetes. All tests were two-sided and the significance level for all analyses was set to p < 0.05. Results The prevalence of alcohol consumption among persons with diabetes was 23.45% [95% CI: 18.9-28.7%]. Divorced, separated and widowed patients (Adj PR: 0.42, 95% CI: 0.21-0.83); and Protestant (Adj PR: 0.44, 95% CI: 0.24-0.82); Muslim (Adj PR: 0.30, 95% CI: 0.14-0.62); and Pentecostal (Adj PR: 0.32, 95% CI: 0.15-0.65) patients were less likely to consume alcohol. Diabetic patients who had a diabetes duration greater than 5 years were more likely to consume alcohol (Adj PR: 1.90, 95% CI: 1.25-2.88). Conclusion Approximately one-quarter of participants consumed alcohol. However being catholic, never being married and having diabetes for more than 5 years predisposed persons with diabetes to alcohol consumption. Sensitization messages regarding alcohol consumption among persons with diabetes should be target patients who have never been married and those who have spent more than 5 years with diabetes; religion should also be considered as an important venue for health education in the community.